Pengembangan Media Visual Non Digital pada Siswa Kelas 5 Sekolah Dasar - Chika Puteri Margareta (Indonesian Journal Publisher, 2026)
This study aims to develop non-digital visual learning media in the form of a water cycle diorama and test its feasibility and effectiveness in learning Natural Sciences (IPA) in 5th grade Elementary Schools. The background of the study is based on the low effectiveness of student learning in understanding the abstract concept of the water cycle due to the dominant use of conventional methods and the lack of concrete learning media. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 5th grade students and teachers of SDS Muhammadiyah Ngoro. Data collection techniques include observation, interviews, and questionnaires, while the assessment instrument is used for validation from media experts, material experts, and teacher and student responses. The results of the study indicate that the water cycle diorama media obtained a very high level of validity from media experts and material experts with a percentage of 100%. In addition, the results of student responses showed an effectiveness level of 99% and teacher responses of 100%, which is included in the very effective category. The water cycle diorama media is able to increase active involvement, learning motivation, and conceptual understanding of students towards the water cycle material. Thus, it can be concluded that non-digital visual media in the form of a water cycle diorama is feasible and effective to be used as an alternative science learning media for grade V of Elementary School.